2015
DOI: 10.4172/2329-6887.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tenofovir/Emtricitabine/Efavirenz with and without Chloroquine in Patients with HIV/AIDS C3: Double Blinded Randomized Clinical Trial

Abstract: Background: The use of antiretroviral therapy (ART) reduces both mortality and morbidity of patients with HIV/ AIDS. The effects of chloroquine against HIV replication are widely known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this context, Vero E6 cells were infected with a common human pathogen, the herpes simplex virus type 1 (HSV-1). The antiviral activity of CQ has been reported in the literature [18,19,20,21,22,23,24]. However, its anti-HSV-1 activity was not yet been well described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Vero E6 cells were infected with a common human pathogen, the herpes simplex virus type 1 (HSV-1). The antiviral activity of CQ has been reported in the literature [18,19,20,21,22,23,24]. However, its anti-HSV-1 activity was not yet been well described.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, this work focused on the role of CQ, which is a highlighted lysosomotropic drug among the molecules with proved antiviral activity [18,19,20,21,22,23,24,63]. The CQ has shown pronounced antiviral action against different viruses [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This response is unexpected due to the fact that these women were receiving ARV treatment, which decreases the HIV viral load and neutralises the hyperinflammatory response mediated from the complement system [33] . Moreover, studies by Isaac et al [28] and Datta et al [34] , have reported elevated C3 concentration levels following ARV therapy. ARV’s reduce the viral replication drastically, resulting in decreased circulating viral antigens, antibodies and subsequently leading to the increase of C3.…”
Section: Arv Therapymentioning
confidence: 98%
“…The mechanism of action for most ARV drugs is to inhibit one out of the two HIV enzymes, viz ., protease or transcriptase [28] . The most frequently recommended antiretroviral therapy for initial treatment is Efavirenz + 2 nucleoside reverse transcriptase inhibitors (NRTIs) [29] , one of the drugs of choice administered as combination therapy in our study.…”
Section: Arv Therapymentioning
confidence: 99%